Possible existence of triaxial superdeformation in ^172,174,176W - 董永胜 于少英 沈彩万 刘艳鑫 (Chinese physics C, 2009)
Two-dimensional total routhian surface （TRS） calculations are carried out to determine the triaxial superdeformation （TSD） of the even-even nucleus 174W, and the result indicates that TSD state exists with deformation parameters ε2=0.42 andγ=34.7°. In the same way, the total routhian surfaces for the nuclei ^172,176W are also calculated. It shows that the neutron shell correction energy plays a key role in the formation of TSD nuclei ^172,174,176W, while the high j intruder orbitals and rotational energy are also crucial in the formation mechanism.